Pathways and influencing factors of global competence in Chinese higher vocational education: A systematic literature review - Xing, FENG; Azman, Norzaini; Chen, YANG (Edelweiss Applied Science and Technology, 2025)
In the context of economic globalization and industrial transformation, this study aims to explore how Chinese higher vocational education (HVE) cultivates students’ global competence to meet international labor market demands. Following the PRISMA 2020 guidelines for systematic reviews, twelve eligible studies published between 2010 and 2025 were analyzed using thematic analysis to trace the evolution, main pathways, and influencing factors of global competence cultivation. Findings indicate that research in this area has grown steadily since 2018, focusing on four core themes: empirical investigations, curriculum and pedagogy, teaching materials, and policy strategies. Cultivation pathways are concentrated in three domains: curricular and instructional reform, experiential practice, and campus culture with institutional support. However, challenges persist, including goal-orientation bias, limited faculty capacity, unequal opportunity structures, and mismatches with industry needs. Overall, existing studies remain constrained by limited representativeness, insufficient theoretical localization, and underdeveloped assessment frameworks. Future research should broaden disciplinary and regional coverage, adopt longitudinal and mixed-method approaches, and establish multidimensional evaluation systems aligned with vocational contexts to advance the internationalization and high-quality development of Chinese HVE.